QUR’ANIC SELF-CARE AS AN EFFORT TO OVERCOME BURNOUT: A Study of Hamka’s Tafsir Al-Azhar using the PERMA Approach: SELF-CARE QUR’ANI SEBAGAI UPAYA MENGATASI BURNOUT: Studi Tafsir Al-Azhar Karya Hamka dengan Pendekatan PERMA - Nuha, Ulin; Tassela, Ghina; Binti Mohd Adnan, Nur Syakirah (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
Burnout has emerged as a significant psychological phenomenon in modern life, driven by prolonged work pressure and an imbalance between professional demands and personal needs. This condition calls for an approach that is not only psychological but also spiritual. This article aims to examine the concept of Qur’anic self-care in Tafsir al-Azhar by Hamka and to analyze its relevance to the PERMA model of psychological well-being developed by Martin Seligman. This study employs a library research method with a thematic (maudhu‘i) exegesis approach, using Tafsir al-Azhar as the primary source and relevant scholarly literature as secondary sources. Data are analyzed descriptively and analytically through the integration of Qur’anic interpretation and psychological perspectives. The findings indicate that Hamka’s interpretation of self-care-related verses reflects an integral framework encompassing spiritual, emotional, social, and physical dimensions. Values such as brotherhood (ukhuwah), life balance, self-regulation, and trust in divine ease amid hardship function as adaptive mechanisms in coping with burnout. These findings demonstrate a strong alignment with the five elements of PERMA: positive emotion, engagement, relationships, meaning, and accomplishment. However, notable ontological and epistemological differences remain. PERMA is oriented toward well-being as an ultimate goal grounded in empirical research, whereas in Hamka’s perspective, well-being is a by-product of servitude (‘ubudiyyah) to God, rooted in revelation. This study contributes to the formulation of an integrative Qur’anic self-care model and offers an epistemological bridge between Islamic thought and positive psychology in addressing burnout.